Assessing the sales effectiveness of differently located endcaps in a supermarket. (July 2018) - Tan, Pei Jie; Corsi, Armando; Cohen, Justin; Sharp, Anne; Lockshin, Larry; Caruso, William; Bogomolova, Svetlana
Abstract: This paper compares the sales effectiveness of front versus back located end-of-aisle promotional displays (endcaps) in a supermarket, through measuring sales from the endcaps alone, as well as total brand sales, across three experiments. This paper reveals that rear endcaps generate a higher total brand sales uplift than front endcaps, acting like "billboards" to draw shoppers into the main aisle. On average, rear endcaps generated 416% sales uplift, while front endcaps generated 346% sales uplift. However, front endcaps deliver higher endcap-only sales uplift. These findings challenge industry assumptions about one of the most commonly used promotional tools.